تمايز الذات وعلاقته بالصلابة النفسية لدى أساتذة التعليم الابتدائي: دراسة ميدانية على عينة من أساتذة التعليم الابتدائي بدائرة العمارية لولاية المدية - أوباجي، محمد; مصطفى، عبدالنور مولاي (المركز الجامعي سي الحواس بريكة, 2023)
استهدفت الدراسة الحالية الكشف عن العلاقة بين تمايز الذات والصلابة النفسية لدى أساتذة التعليم الابتدائي، تكونت العينة من 70 أستاذ وأستاذة (22 ذكور، 48 إناث)، تم اختيارهم بطريقة عشوائية بسيطة من مدارس دائرة العمارية لولاية المدية، كما تم استخدام مقياسين هما مقياس تمايز الذات المعد من قبل الكعبي (2007)، والمعدل من طرف الجباري (2013)، مقياس الصلابة النفسية المعد من قبل مخيمر (2002)، والمعدل من طرف الشمري (2015)، كذلك تم استخدام المنهج الوصفي لتناسبه وطبيعة الدراسة، وبعد تطبيق نظام الحزمة الإحصائية والاجتماعية (spss) أسفرت النتائج على: وجود علاقة ارتباطية موجبة دالة إحصائيا بين تمايز الذات والصلابة النفسية، وجود فروق في درجة الصلابة النفسية بين أساتذة التعليم الابتدائي لصالح الذكور، لا توجد فروق بين أساتذة التعليم الابتدائي (ذكور -إناث) في متغير تمايز الذات. The current study aimed at revealing the relationship between self differentiation and psychological hardness among teachers of primary education. The sample consisted of 70 male and female teachers (22 males, 48 females), who were chosen randomly from the schools of the Amariya district of the state of Medea. Two scales were used: the self-differentiation scale Prepared by Al- Kaabi (2007), and modified by Al-Jabari (2013), the psychological hardness scale prepared by Mukhaimer (2002), and modified by Al-Shammari (2015). The descriptive approach was used to suit it and the nature of the study, and after applying the statistical and social package system (spss) The results revealed: There is a statistically significant positive correlation between self-differentiation and psychological hardness, and there are differences in the degree of psychological hardness among primary education teachers in favor of males. There are no differences between primary education teachers (males-females) in the self-differentiation variable.
Keywords: العملية التربوية -- الاحتراق النفسي -- التماسك الأسري -- الاضطرابات النفسية